Adding dexamethasone to intrathecal bupivacaine 0.5%; comparing the anesthetic ability with bupivacaine 0.5% alone among cesarean section patients - Seyed Mohammad Nasirodin Tabatabaei; Alireza Rahat-Dahmarde; Jamshid Ordoni Avval; Hossein Ali Khazaie (Medičnì Perspektivi, 2022)
A perfect anesthesia technique is one in which anesthesia can be done in the shortest possible time with minimal hemodynamic changes and side effects This study is aimed to investigate the effects of concomitant administration of dexamethasone with bupivacaine on the duration of anesthesia and the quality of anesthesia-induced in patients undergoing cesarean section. This is a quasi-experimental study done on patients undergoing cesarean section by spinal anesthesia. All patients underwent standard monitoring after admission, then Ringer serum (5 cc/kg) was administered to the patients. The patients was then seated and subjected to intrathecal anesthesia with a midline approach in L3-L4 space. Patients were matched for baseline conditions. After recording background information, type and dosage of drugs used, blood pressure, heart rate, number and frequency of nausea and vomiting were listed in the checklist, and the data were analyzed using SPSS software. In this study, 70 pregnant women who were candidates for cesarean section were included. All our studied parameters, including the mean time to the start of  analgesia, mean time of analgesia duration, analgesia duration, mean time to first request for analgesics were significantly improved among the intervention group. The use of dexamethasone and bupivacaine to induce spinal anesthesia during cesarean section can significantly shorten the onset time of analgesia and reduce postoperative nausea and vomiting. Dexamethasone can be used as an effective drug in cesarean section.